Fatty liver disease reverses the obesity paradox in chronic kidney disease stages 3–5: A follow‐up study of NHANES III. Issue 11 (20th September 2022) - Huang, Jiaofeng; Zhang, Min; Wu, Yinlian; Wang, Mingfang; Zhu, Yueyong; Lin, Su
Abstract: High body mass index (BMI) has been associated with better survival in patients with end‐stage kidney disease. Individuals with fatty liver disease (FLD) have a higher risk of chronic kidney disease. It remains unclear whether the survival benefit of high BMI in patients with chronic kidney disease is present when there is concomitant FLD. This study used the data set from the Third American National Health and Nutrition Examination Survey and the corresponding survival data. The Cox proportional hazards model was used to evaluate the effect of BMI on mortality. A total of 12, 445 participants were included. The prevalence of FLD was 39.8%. The median follow‐up time (with interquartile range) was 22.8 (20.8–24.8) years. During this period, 3749 (30.1%, 14.4 of 1000 person‐year) deaths were observed. Among these, 1169 (31.2%) died within the first 10 years. The Cox regression analysis showed that the BMI level was not associated with 25‐year mortality in patients with decreased glomerular filtration rate (GFR < 60 ml/min/1.73 m 2 ), but 10‐year mortality was significantly lower in patients with BMI ≥ 25 kg/m 2 than in those with BMI < 25 kg/m 2 ( p  = 0.049). Multivariate analysis showed BMI ≥ 25 kg/m 2 was an independent protective factor for 10‐year mortality (hazard ratio [HR] 0.691, 95% confidence interval [CI] 0.559–0.856; p  = 0.001). This protective effect of higher BMI was lost in patients with FLD (HR 0.884, 95% CI 0.585–1.335; p  = 0.557) but persisted in the non‐FLD group (HR 0.625, 95% CI 0.479–0.816; p  = 0.001). The survival benefit of overweight/obesity for patients with decreased GFR, which was attenuated by the presence of FLD, only existed in the first decade.